MicroRNA target homeobox messenger RNA in HIV induced hematopoietic inhibition - Koka, Prasad S.; Ramdass, Bharathi (Frontiers in Cell and Developmental Biology, 2024)
Cytopenias are a common occurrence due to abnormal hematopoiesis persistent in patients suffering and advancing with HIV/AIDS. In order to develop efficacious therapies against cytopenias, it is necessary to understand the mechanisms of how HIV infection affects differentiation of the Hematopoietic Stem-Progenitor Cells (HSPC) causing hematopoietic inhibition that leads to hematological disorders. Currently, only the antiretrovirals that are being used to treat HIV infection and contain this virus replication, indirectly lower the levels of or co-attenuate cytopenias as well. Evidence available suggests that this indirect efficacy may not prevail for the lifetime of the infected patients and the acquired immunodeficiency can overtake the beneficial consequences of decreased virus replication. As reported earlier and cited herein, we are the first to make a foray into the microRNA involvement as potential interventional treatments for the cytopenias that occur in HIV/AIDS. Herein, we progressed further in the direction of the mechanisms of involvement of the homeobox gene regulation to cause cytopenias. We had previously shown that HIV-1 inhibits multilineage hematopoiesis of the CD34+ cells using SCID-hu Thy/Liv animals in vivo. Further, we had demonstrated that the virus induced hematopoietic inhibition occurred despite the CD34+ cells being resistant to HIV-1 infection. We set out the search for the specific host factors secreted by CD4+ T-cells likely participate in the inhibition of hematopoiesis of the HIV infection-resistant CD34+ cells. More recently, we reported the identification of virus-infected CD4+ thymocyte-secreted miRNA-15a and miRNA-24 and that their differential expression following HIV infection, causes the indirect inhibition of hematopoiesis. We then hypothesized that the observed miRNA differential expression in the virus-infected T-cells, causes abnormal regulation of homeobox (HOX) gene encoded transcriptomes in the CD34+ cells, affecting specific MAPK signaling and CD34+ cell-fate, thereby causing disruption of normal hematopoiesis. We present that in HIV infection, miRNA-mediated posttranscriptional dysregulation of HOXB3 mRNA inhibits multi-lineage hematopoiesis, that translates into hematological disorders in virus-infected patients of HIV/AIDS. These observations portend specific microRNA candidates for efficacy against the virus induced cytopenias that are otherwise not treatable by the existing HAART/ART regimens that are primarily designed for efficacy to attain attenuation of virus replication.